Peer learning-making use of sociocultural theory. (July 2020) - Carlson, Elisabeth; Stenberg, Marie
Highlights: Collaborative ways of learning are increasingly popular in nursing education. Peer Learning is just one example presenting several benefits for student learning. Theoretical underpinnings of educational models need to be discussed. Sociocultural theory is a good fit for peer learning as it focus student activity.